Functional Diversity of Transcriptional Regulators in the Cyanobacterium Synechocystis sp. PCC 6803 - Shi, Mengliang; Zhang, Xiaoqing; Pei, Guangsheng; Chen, Lei; Zhang, Weiwen (Frontiers in Microbiology, 2017)
Functions of transcriptional regulators (TRs) are still poorly understood in the model cyanobacterium Synechocystis sp. PCC 6803. To address the issue, we constructed knockout mutants for 32 putative TR-encoding genes of Synechocystis, and comparatively analyzed their phenotypes under autotrophic growth condition and metabolic profiles using LC-MS-based metabolomics. The results showed that only four mutants of TR genes, sll1872 (lytR), slr0741 (phoU), slr0395 (ntcB) and slr1871 (pirR), showed differential growth patterns in BG11 medium when compared with the wild type; however, in spite of no growth difference observed for the remaining TR mutants, metabolomic profiling showed that they were different at the metabolite level, suggesting significant functional diversity of TRs in Synechocystis. In addition, an integrative metabolomic and gene families analysis of all TR mutants led to the identification of five pairs of TR genes that eachshared close relationship in both gene families and metabolomic clustering trees, suggesting possible conserved functions of these TRs during evolution. Moreover, more than a dozen pairs of TR genes with different origin and evolution were found with similar metabolomic profiles, suggesting a possible functional convergence of the TRs during genome evolution. Finally, a protein-protein network analysis was performed to predict regulatory targets of TRs, allowing inference of possible regulatory gene targets for 4 out of five pairs of TRs. This study provided new insights into the regulatory functions and evolution of TR genes in Synechocystis.